Stochastic Contracts and Subjective Evaluations - Matthias Lang (Center for Economic Studies and ifo Institute (CESifo), 2021)
Subjective evaluations are widely used, but call for different contracts from traditional moral-hazard settings. Previous literature shows that contracts require payments to third parties, which real-world contracts rarely use. I show that the implicit assumption of deterministic contracts makes payments to third parties necessary. This paper studies stochastic contracts, like uncertain arbitration procedures or payments in stock options. These contracts incentivize employees without the need for payments to third parties. In addition, stochastic contracts can make the principal better off compared to deterministic contracts. My results also address the puzzle about the prevalence of labor contracts with stochastic compensation.
Keywords: D80; J41; J70; 330; subjective evaluations; stochastic contracts; budget-balanced contracts; moral hazard; subjective performance measures; incentives